HUBUNGAN FAKTOR INTERNAL & EKSTERNAL DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU WFH DI MASA PANDEMI COVID 19 - Andayani, Cici Mela; Afiyanti, Yati (Nusantara Hasana Journal, 2022)
During the covid 19 pandemic, working mothers were required to work from home due to government regulations so that mothers had enough time to be with their babies and were able to breastfeed their babies. Method: : This type of research is descriptive correlative, with a cross sectional approach, the sampling technique of this study is total sampling with a sample of 112 people in this study. The data analysis technique used is multiple linear regression by looking at the chi square test of the Pearson moment value. Results: At a significance level of 5%, it shows that: the work variable with a value (p = 0.518> 0.05) with a very weak correlation level of 0.007. Socio-economic (p=0.147>0.05) with a very weak relationship level of 0.044. Sources of information (p=0.111>0.05) the correlation level is -0.150 with a very weak degree of relationship. Husband's support (p<0.0001 means <0.05) with a correlation level of 0.390 which means the relationship level is moderate. Conclusions: Employment, socio-economic variables, and sources of information have no relationship with the success of exclusive breastfeeding for wfh mothers during the covid-19 pandemic in Indonesia. Meanwhile, husband's support has a significant relationship with the success of exclusive breastfeeding for WFH mothers during the COVID-19 pandemic in Indonesia.